Auditory exposure of high‐risk infants discharged from the NICU and the impact of social factors. (10th March 2020) - Liszka, Lara; Heiny, Elizabeth; Smith, Joan; Schlaggar, Bradley L.; Mathur, Amit; Pineda, Roberta
Abstract: Aim: To (a) define the early home auditory environment of high‐risk infants within one month of neonatal intensive care unit (NICU) discharge, (b) compare auditory exposures in the home environment to the NICU environment,   and (c) define relationships between maternal/infant factors and auditory exposures within the home. Methods: Seventy‐three high‐risk infants (48 high‐risk infants in the NICU at term‐equivalent age and 25 high‐risk infants in the home following NICU discharge) had auditory exposures measured. Results: An average of 1.3 hours more noise ( P  ≤ .001) and 2 hours less silence ( P  = .01) were observed in the NICU compared with the home, but differences varied based on whether comparing to an open ward or private room. Infants with public insurance, lower household income and mothers without a college education were exposed to an average of 2.8, 3.0 and 2.3 hours more TV/electronic sounds respectively ( P  < .05). An average of 1744 fewer adult words ( P  = .03) were spoken in households with public insurance. There was an average of 3.1 hours less silence and 4.5 dB louder stimuli among households with lower income ( P  < .05). Conclusion: Elucidating differences across environments can lead to interventions to foster appropriate auditory exposures to improve language development of high‐risk infants.